A Complementary Toolbox of Iterative Methods for the Stereoselective Synthesis of Heteroatom-Rich Motives from C1-Building Blocks - Kirupakaran, Sujenth; Korth, Hans-Gert; Hirschhäuser, Christoph (Synthesis, 2018)
The ability to assemble organic molecules one carbon atom at a time has been a long-held dream for chemists. Modern boronate homologations with chiral carbenoids allow for the assembly-line synthesis of long chiral alkyl chains with excellent control over individual stereocenters. Nevertheless, heteroatom rich motives present a serious synthetic challenge to this approach. Interestingly, older methods based on substrate-controlled homologations of chiral boronic esters or umpolung of a carbonyl nucleophile can offer complementary solutions. A combination of these approaches might thus extend the range of possible targets currently within grasp of a C1-based synthesis. Link to video abstract: https://www.youtube.com/watch?v=PH_HBrqQwtg .1 Introduction2 Substrate Control: Stereoselective Addition of d1-Reagents to Aldehydes3 Stereocontrol by Chiral Auxiliary/Director: The Matteson Boronate Homologation4 Reagent Control: Moving Chiral Information to the Carbenoid5 Conclusions and Outlook
Keywords: homologation; assembly-line synthesis; chiral carbenoid; boronic ester; Matteson homologation; Dondoni homologation; Aggarwal homologation